Implementasi Peraturan Bupati Aceh Tamiang Nomor 14 Tahun 2016 Tentang Pelimpahan Sebagian Kewenangan Bupati Kepada Camat - Hidayat, Renir; Badaruddin, Badaruddin; Warjio, Warjio; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
This research is to find out the efforts of the sub-district government itself in improving its services within the framework of meeting the needs of its citizens. This study uses a qualitative descriptive method that is a study by using data obtained through observation, interviews and documentation. The results of the study found that the obstacles in implementing Aceh Tamiang District Regulations Number 14 Year 2016, namely in carrying out the transfer of some of the Regent's authority to the District Head through the District Integrated Administration Services that have not been maximally provided to the community, can be seen from the PATEN assessment conducted by the Regency Government towards the District Government. This has several inhibiting factors, namely the lack of qualified human resources, the availability of inadequate budgets and is described from Hamdi's theory, namely from the productivity dimension, the Linearity Dimension, and the Efficiency Dimension. As well as having factors that influence, among others, Policy Sustansi, Implementing Task Behavior, Work Network Interaction, Target Group Participation, and Resources.